Alligator and Crocodile Research - Center for Natural Resources (EDIS, 2003)
A quarterly publication of the Center for Natural Resources. The mission of the Center for Natural Resources is to resolve natural resource and environmental issues through multi-disciplinary collaborations among UF faculty & external stakeholders. Volume 3,  issue 12. Published November 2002.